The Increasing Challenge of Multidrug-Resistant Gram-Negative Bacilli: Results of a 5-Year Active Surveillance Program in a Neonatal Intensive Care Unit. Issue 10 (March 2016) - Giuffrè, Mario; Geraci, Daniela M.; Bonura, Celestino; Saporito, Laura; Graziano, Giorgio; Insinga, Vincenzo; Aleo, Aurora; Vecchio, Davide; Mammina, Caterina
Abstract : Abstract: Colonization and infection by multidrug-resistant gram-negative bacilli (MDR GNB) in neonatal intensive care units (NICUs) are increasingly reported. We conducted a 5-year prospective cohort surveillance study in a tertiary NICU of the hospital "Paolo Giaccone, " Palermo, Italy. Our objectives were to describe incidence and trends of MDR GNB colonization and the characteristics of the most prevalent organisms and to identify the risk factors for colonization. Demographic, clinical, and microbiological data were prospectively collected. Active surveillance cultures (ASCs) were obtained weekly. Clusters of colonization by extended spectrum β-lactamase (ESBL) producing Escherichia coli and Klebsiella pneumoniae were analyzed by conventional and molecular epidemiological tools. During the study period, 1152 infants were enrolled in the study. Prevalences of colonization by MDR GNB, ESBL-producing GNB and multiple species/genera averaged, respectively, 28.8%, 11.7%, and 3.7%. Prevalence and incidence density of colonization by MDR GNB and ESBL-producing GNB showed an upward trend through the surveillance period. Rates of ESBL-producing E coli and K pneumoniae colonization showed wide fluctuations peaking over the last 2 years. The only independent variables associated with colonization by MDR GNB and ESBL-producing organisms and multiple colonization were, respectively, the days of NICU stay (odds ratio [OR] 1.041), the days of exposure to ampicillin–sulbactam (OR 1.040), and the days of formula feeding (OR 1.031). Most clusters of E coli and K pneumoniae colonization were associated with different lineages. Ten out of 12 clusters had an outborn infant as their index case. Our study confirms that MDR GNB are an increasing challenge to NICUs. The universal once-a-week approach allowed us to understand the epidemiology of MDR GNB, to timely detect new clones and institute contact precautions, and to assess risk factors. Collection of these data can be an important tool to optimize antimicrobials use and control the emergence and dissemination of resistances in NICU.